Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/wer.10728
|View full text |Cite
|
Sign up to set email alerts
|

Mainstream partial denitrification‐anammox in sand and expanded clay deep‐bed polishing filters under practical loading rates and backwashing conditions

Abstract: This study focused on evaluating the feasibility of expanded clay and sand as media types for mainstream partial denitrification‐anammox (PdNA) in deep‐bed single‐media polishing filters under nitrogen and solids loading rates as well as backwash conditions similar to conventional denitrification filters. The surface roughness and iron content of the expanded clay were hypothesized to allow for enhanced anammox retention, nitrogen removal rates, and runtimes. However, under the tested loading rates and backwas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 46 publications
6
19
1
Order By: Relevance
“…In mainstream shortcut nitrogen removal systems, a recent study by Van Winckel et al (2019) emphasized the importance of anammox retention for success. One‐stage PdNA applications have been tested so far in MBBRs (Campolong et al, 2019; Gu et al, 2020; Ma et al, 2017) and downflow filters (Fofana, Chen, et al, 2021; Klaus, 2020; Ma et al, 2020; Young et al, 2021), but studies with an IFAS application under real wastewater conditions are limited or missing to the best of our knowledge. One of the benefits offered by an IFAS configuration is the ease and flexibility of implementation into new and existing systems.…”
Section: Introductionmentioning
confidence: 99%
“…In mainstream shortcut nitrogen removal systems, a recent study by Van Winckel et al (2019) emphasized the importance of anammox retention for success. One‐stage PdNA applications have been tested so far in MBBRs (Campolong et al, 2019; Gu et al, 2020; Ma et al, 2017) and downflow filters (Fofana, Chen, et al, 2021; Klaus, 2020; Ma et al, 2020; Young et al, 2021), but studies with an IFAS application under real wastewater conditions are limited or missing to the best of our knowledge. One of the benefits offered by an IFAS configuration is the ease and flexibility of implementation into new and existing systems.…”
Section: Introductionmentioning
confidence: 99%
“…Only one genus of AnAOB was found in the filters, Candidatus Brocadia, which has been frequently identified in PdNA systems (Cui et al, 2020; Du et al, 2019; Fofana, Huynh et al, 2022; Lu et al, 2021; Schoepflin et al, 2022; Wang et al, 2020; Wang, Xu et al, 2020; Zhan et al, 2020; Zheng, et al, 2020). The relative abundance of Candidatu s Brocadia (2–5%) obtained in the filters was significantly higher than other one‐stage PdNA filters (0.7–1.0%) (Cao et al, 2020; Lu et al, 2021), most likely due to the higher loading rates at full‐scale.…”
Section: Resultsmentioning
confidence: 99%
“…To maintain AnAOB activity during normal operation right after a backwash, sufficient methanol needs to be provided to decrease the DO and ensure that the top of the filters is fully anoxic while at the same time avoid methanol overdose. While there are early reports that methanol can be inhibitory to AnAOB (Güven et al, 2005;Isaka et al, 2008), recent experiences in methanol PdNA process has shown no anammox inhibition (Bachmann et al, 2021;Campolong et al, 2019;Fofana et al, 2021;Macmanus et al, under review) even under temporal methanol concentration of 200 mg COD/L (Campolong et al, 2019). However, avoiding methanol overdose is also important in order to maintain a consistent NO 3 À -N residual to encourage PdN.…”
Section: Pdna Phase: Impact Of Runtime On Pdnamentioning
confidence: 99%
See 2 more Smart Citations